Undergraduates’ Achievement Goal Orientations, Academic Self-Efficacy and Hope as the Predictors of Their Learning Approaches - KALI SOYER, MAKBULE (My University, 2019)
The aim of the present study was to figure out whether university students’ learning approaches were shaped via their achievement goal orientations, academic self-efficacy and hope or not. The other objective was to examine if these psychological constructs varied in accordance with the demographic variables including gender, age and class level. 332 undergraduates from two different universities who were in the year of junior and senior participated in the study. The Achievement Goal Orientations Scale, the Academic Self-Efficacy Scale, the Dispositional Hope Scale and the Demographic Form were utilized to reveal the predictive power of these constructs on their learning attitudes measured by the Revised Two-Factor Study Process Questionnaire. Multiple linear regression analysis indicated that learning goal orientation was a pivotal predictor of both deep and surface approach to learning. Academic self-efficacy and hope were the crucial precursors of deep approach while performance-avoidance goal inclination was a considerable predictor of surface approach. Independent samples t-test analysis displayed that the female undergraduates were superior to the male ones in terms of the learning goal tendency. And the students (20 to 22 aged) demonstrated higher scores on the same variable than the other ones (23 to 25 aged). On the basis of class level, there were no significant differences in the scores of achievement goal orientations, academic self-efficacy, hope and learning approaches. The results pointed out the fact that such concepts pertinent to an undergraduate’s academic performance could be viewed as distinctive features engendering different learning attitudes toward scholastic training.